2009
DOI: 10.1016/j.cancergencyto.2009.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal changes in aggressive breast cancers with basal-like features

Abstract: Using high-resolution oligonucleotide CGH arrays, we evaluated chromosomal copy number changes in a series of 16 breast cancers, selected on the basis of highly similar pathological and molecular features characteristic of the "basal-like" phenotype. Each of these cancers showed numerous gains and losses, reflecting multiple chromosomal rearrangements during the development of these high-grade cancers. Chromosomal losses were particularly prevalent on chromosomal arms 5q, 8p, 9q, 12q, 17p, 19p, and Xq, and gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
(31 reference statements)
1
37
0
Order By: Relevance
“…We compared the findings on our series (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc= GSE23891) with those found on a female breast cancer dataset deposited with the Gene Expression Omnibus (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc= GSE12659) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the findings on our series (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc= GSE23891) with those found on a female breast cancer dataset deposited with the Gene Expression Omnibus (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc= GSE12659) [32].…”
Section: Discussionmentioning
confidence: 99%
“…ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE12659), to which the same algorithms have been applied [32]. Among datasets available online this has been chosen being, in our opinion, the most comparable to ours in terms of number of cases and platform of analysis.…”
Section: Microarray Data Analysismentioning
confidence: 99%
“…We have previously shown that high protein expression of VEGFR2 is significantly correlated to poor survival in TNBC (Ryden et al, 2010). Genomic aberrations of VEGFR2 or KIT have not previously been investigated in TNBC tumors, but high-level amplification of the 4q12 region was reported in a small sample set of basal-like breast cancers (Yu et al, 2009). In the present study, we investigated 31 TNBC and 50 non-TNBC tumors for copy number gains of VEGFR2 and KIT, as well as the protein expression of KIT.…”
Section: Discussionmentioning
confidence: 96%
“…In human disease, the mechanisms by which α 2 integrin subunit gene expression is decreased in cancer are unknown. The human α 2 integrin gene lies on chromosome 5q23, a site of frequent deletions in breast cancer (45). However, deletion of the α 2 integrin gene in cancer has not been reported.…”
Section: Figurementioning
confidence: 99%